Symptom Chronicity and its Association with Functional Outcomes after Carpal Tunnel Release at a Tertiary Care Center: A Cross-Sectional Study - Shrestha, Ram Chandra; KC, Raj Kumar; Mahaseth, Adarsha; Aryal, Sameer (Nepal Journal of Neuroscience, 2025)
Background: Carpal tunnel syndrome is the most common entrapment neuropathy and has a substantial impact on occupational performance and quality of life. Carpal tunnel release is the standard treatment for moderate to severe cases, but the influence of symptom chronicity on surgical outcomes is not well established.Objective: To assess the association between symptom chronicity and functional outcomes, patient satisfaction, return to work, and complication rates following carpal tunnel release at a tertiary care center.Methods: This prospective observational study included fifty patients undergoing carpal tunnel release. Participants were stratified into three groups according to duration of symptoms: less than six months, six to twelve months, and more than twelve months. Functional outcomes were measured using the Boston Carpal Tunnel Questionnaire before and six months after surgery. Patient satisfaction was assessed with the Patient Global Impression of Improvement scale. Electrophysiological recovery, complication rates, and time to return to work were also analyzed.Results: Patients with symptom duration less than six months showed the greatest improvement in functional scores, highest satisfaction, and shortest return to work time. Longer symptom duration was associated with higher preoperative severity, lower postoperative satisfaction, slower recovery, and more complications. Electrophysiological improvement was observed across all groups but was most pronounced in patients with shorter symptom duration.Conclusion: Symptom chronicity significantly influences outcomes after carpal tunnel release. Early surgical intervention within six months of symptom onset results in better recovery, greater satisfaction, fewer complications, and faster return to work.